Pengaruh Leadership terhadap Kinerja Karyawan melalui Kepuasan Kerja PT Pegadaian Area Pamekasan - Ade Syahrizal Trisnawan; Indra Prasetyo; Chamariyah Chamariyah (Universitas 45 Surabaya, 2025)
Ade Syahrizal Trisnawan, 2025. Influence Leadership Towards Performance Employee Through Satisfaction Work of PT. Pegadaian Pamekasan Area. Graduate program University Wijaya Putra Surabaya. Based on his approach study This including in type study explanatory research. Sample study as many as 84 respondents. Objective study This is: 1) For test And analyze whether Leadership influential to Satisfaction Work at the Pawnshop Office Pamekasan Area Sharia 2) For test And analyze whether Leadership influential to Performance Employee at the Pamekasan Area Pawnshop Office 3) For test And analyze whether Satisfaction Work influential to Performance Employee at the Pamekasan Area Pawnshop Office 4) For test And analyze whether Leadership influential in a way No direct to Performance Employee at the Pamekasan Area Pawnshop Office which was mediated by satisfaction work. Results study show that: 1) Leadership influential significant to Satisfaction Work at the Pawnshop Office Pamekasan Area Sharia with mark original sample of 0.461. 2) Leadership influential significant to Performance Employee at the Pamekasan Area Pawnshop Office with mark original sample of 0.610. 3) satisfaction Work influential significant to Performance Employee at the Pamekasan Area Pawnshop Office with mark original sample of 0.300. 4) Leadership influential significant to to Performance Employee at the Pamekasan Area Pawnshop Office which was mediated by satisfaction Work with mark original sample of 0.138.